ORGANIZATIONAL COMMUNICATION PATTERNS OF KAIZEN TEAM IN POINT BLANK ONLINE GAME - Aprio, Aqza Araieza; Athalarik, Fadli Muhammad (Acta Diurna: Jurnal Ilmu Komunikasi, 2024)
The advancement of internet technology, one of its benefits is being used for entertainment, such as video games and online games. In some online games, there are various teams competing against each other to achieve specific goals. Not all online games have good in-game voice communication, and some lack this feature, like the online game Point Blank. The issue faced by Point Blank players is t he difficulty in finding suitable and practical means of interaction. This research aims to analyze the application of Discord in maintaining communication patterns within the Kaizen Team Organization in an Online First Person Shooter (FPS) game. The method used in this research is qualitative descriptive with observation, interviews, and documentation techniques. Based on the conducted research, Discord communication media utilized by the Kaizen Team Organization is considered effective during Point Blank gameplay. The communication process helps facilitate message delivery. The results of this research indicate that the suitable and effective communication for the Kaizen Team involves the communication patterns of All-Channel, Wheel, and Y. Furthermore, two different types of organizational communication implementation were found within the Kaizen team, namely informal communication and formal communication.